STRATEGI PENGEMBANGAN USAHA GULA MERAH NIRA KELAPA DI DESA KARANGSARI KECAMATA ADIPALA KABUPATEN CILACAP - Nurti Novita Sari; Sulistyo Sidik Purnomo; I Putu Eka Wijaya (Universitas Galuh, 2023)
This study aims to identify internal and external factors and strategies that can be applied to the development of coconut palm sugar business. This research was conducted in Karangsari Village, Adipala District, Cilacap Regency. The analytical method used is SWOT analysis. Internal strategic factors strengths and weaknesses are: the production process and technology used in practice, the availability of production facilities and infrastructure, diversification, having agents and regular customers, processing is carried out every day, natural sweet taste, the grinder has not been able to access production information, the product does not yet have a label. brands, limited independent business capital, human resources, lack of information on plantation replanting schedules, lack of knowledge about market demand. External strategic factors, opportunities and threats are: market demand is quite high, transportation facilities support distribution, already have a clear market, many healthy lifestyle trends are switching to consuming coconut sap brown sugar as an ingredient in food, the price of coconut sap brown sugar can compete with the market. other sugar products, the existence of a private partnership program for product development, the provision of seeds by the government through extension workers, the existence of a bazaar for the introduction of coconut palm sugar products at certain events, the prices set by agents tend to be low, limited funds for business development from the government, limited access to technology, information , and communication regarding coconut palm sugar, the lack of government support for the export potential of coconut palm sugar products. The strategy that can be applied in the development of coconut palm sugar business is the S-O strategy.